Distribution and sources of organochlorine pesticides in agricultural soils from central China - Zhou, Qun; Wang, Jingjing; Meng, Beidi; Cheng, Junqi; Lin, Guoping; Chen, Jiachun; Zheng, Dan; Yu, Yanhong (Ecotoxicology and environmental safety, 2013)
There is little information on the organochlorine pesticides (OCPs) residues in agricultural soils of Wuhan, the largest city in central China. Surface soil samples were collected from agricultural soils in Wuhan and analyzed to determine twenty-one OCPs. According to the measured concentrations and detection frequencies, dichlorodiphenyltrichloroethanes (DDTs), hexachlorocyclohexanes (HCHs), heptachlor (HEPT), hexachlorobenzene (HCB) and aldrin were the predominant compounds in soil. DDTs accounted for 77.10% of total OCPs, followed by HCHs (7.83%), aldrin (4.21%), HEPTs (2.82%) and HCB (1.53%). The total DDT concentrations ranged from nd to 1198.0ngg−1 and the main contaminated areas were distributed in Hannan and Xinzhou districts of Wuhan. The total HCH concentrations ranged from nd to 100.58ngg−1 in soil and relatively higher levels were observed in soil samples from Huangpi and Hannan districts. Source analysis showed that OCPs residues except heptachlor originated mainly from historical application, besides slight recent introduction at some sites. Based on the China National Soil Quality Standard, DDT pollution in most samples of Wuhan agricultural soils could be considered as no and low contamination, while the level of HCHs was classified as no pollution. Our study indicated that there existed potential exposure risk of OCPs in Wuhan agricultural soils although the use of OCPs has been banned. •OCPs in agricultural soils from central China were determined to evaluate the status of contamination.•HCH pollution in most samples of agricultural soil were considered as no contamination by GB15618-1995.•The level of DDTs was classified as low pollution by GB15618-1995.•OCPs residues except heptachlor originated mainly from historical application.